2018
DOI: 10.1253/circj.cj-17-1464
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcomes of Subintimal vs. Intraluminal Revascularization Approaches for Long Femoropopliteal Occlusions in a Korean Multicenter Retrospective Registry Cohort

Abstract: a totally occluded segment via intentional creation of a subintimal channel. Since this approach was first described by Bolia et al in 1989, 3 the subintimal approach has been widely used to overcome long chronic arterial occlusions. 2,4-6 Furthermore, the more recent introduction of re-entry devices and the adoption of bidirectional wiring approaches have improved the technical success of the subintimal approach for femoropopliteal lesions. 7 In addition, implantation of self-expanding nitinol stents further… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…Previous studies have failed to prove that the intraluminal approach has a clinical benefit compared with the subintimal approach [2][3][4] . However, in these studies, intraluminal and subintimal approaches were classified based on the wiring method and/or the size of the guidewire.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have failed to prove that the intraluminal approach has a clinical benefit compared with the subintimal approach [2][3][4] . However, in these studies, intraluminal and subintimal approaches were classified based on the wiring method and/or the size of the guidewire.…”
Section: Discussionmentioning
confidence: 99%
“… 24) Other comparative studies found no difference in the technical success rates for the 2 strategies. 21) 22) 24) However, Soga et al 22) reported that 25% of the IA cases in their study crossed over to a subintimal approach due to technical difficulties during IA. SA also had a significantly shorter procedure time, lesser use of guidewires, body surface echography, and IVUS.…”
Section: Technical Successmentioning
confidence: 95%
“…Overall, procure-related complication rates do not significantly differ between the 2 endovascular strategies. 20) 22) Only Kim et al 24) reported a higher major complication rate (4.1% vs. 0.4%) with SA. However, they still found similar incidence of distal embolizations and arterial ruptures for the 2 treatments.…”
Section: Procedural Complicationsmentioning
confidence: 97%
See 2 more Smart Citations